Abundance and distribution of endoparasitic helminths in Anabas testudineus (Bloch, 1792) from a polluted beel of Bangladesh (Bangladesh Journal of Zoology, 2015)
Abundance and distribution of the endoparasitic helminths in Anabas testudineus (collected from a polluted water body) was analyzed. Out of 50 fish observed, 42 (84%) were parasitized by at least one species. Five metazoan endoparasites, one trematode (Neopecoelina saharanpuriensis) and four nematodes (Ascaridida sp., Contracaecum sp., Camallanus anabantis and C. pearsei) were recorded. Prevalence was higher in female (90%) hosts than males (75%). A significant positive correlation was observed between the standard length of the host and the abundance for parasites except Ascaridida sp. Nematodes were the more prevalent group (72%) than trematodes (48%). No parasitic species was observed as central species category; three parasites (N. saharanpuriensis, Ascaridida sp. and Contracaecum sp.) were considered as secondary and Camallanus spp. as satellite species. All nematode parasites showed aggregated distribution pattern and the trematode showed random distribution pattern. Interspecies association between two species of parasite was low.Bangladesh J. Zool. 42(1): 1-10, 2014